Metode dan Prosedur Penerjemahan Quote Anime Bahasa Jepang ke dalam Bahasa Indonesia pada Official Akun LINE Bahasa Jepang Bersama - Dwi Ratna Komala, Ida Ayu Made; Dian Aryani, Made Ratna; Anggraeny, Renny (Humanis; Vol 23 No 2 (2019), 2019)
The title of this research is “Method and Procedure of Translation used in Anime Quotes from Japanese to Indonesia at Official Account LINE Bahasa Jepang Bersama”. The purpose of the research is to identify the types of technique, procedure, and method of translation applied in translating anime quotes. Theories used in this research are the theory of translation techniques proposed by Molina and Albir (2002), the procedure of translation by Vinay and Darbelnet (1995), and the translation methods by Newmark (1988). The research data was analyzed by translational equivalence method and glossing. The result of the data analysis indicates that there are several translation techniques applied, they are literal translation, amplification, modulation, linguistic amplification,established equivalence, reduction, and transposition. The most found translation technique is literal translation because its aim is to produce a translation that stick to the originality of the language source text content and form. Then, there are procedures of translation applied, they are literal translation, transposition, and modulation. Thereafter for the method of translation applied they are literal translation, free translation, communicative translation, and idiomatic translation. The most found translation method is free translation because its aim is to produce a translation that fit to the need of target language readers. The translation methods applied tend to be oriented towards the target language.